40AR-39AR AND RB-SR AGE CONSTRAINTS ON THE FORMATION OF SUKHOI-LOG-STYLE OROGENIC GOLD DEPOSITS OF THE BODAIBO DISTRICT (NORTHERN TRANSBAIKALIA, RUSSIA) - Chugaev A.V.; Budyak A.E.; Larionova Yu.O.; Chernyshev I.V.; Travin A.V.; Tarasova Yu.I.; Gareev B.I.; Batalin G.A.; Rassokhina I.V.; Oleinikova T.I. (My University, 2022)
The Bodaibo District (the Irkutsk Region of Russia) is a world-class gold-mining subprovince comprising a total of 13 large- and medium-scale black-shale-hosted orogenic gold deposits known as the Sukhoi Log-style gold deposits (Ivanov, 2014). The gold mineralization of the Sukhoi Log-style deposits is represented by early veinlet-disseminated sulfide ores, which have the main economic significance, and late native gold-bearing quartz veins with only minor gold reserves. This paper presents the results of Rb-Sr и 40Ar-39Ar dating of the gold mineralization in four Sukhoi Log-style deposits: Verninsky, Golets Vysochaishy, Ozherelie, and Ikan, with the estimated gold reserves of 143, 86, 6.5, and 7.0 metric tons, respectively. The Rb-Sr and 40Ar-39Ar data obtained indicate the existence of two ore-forming events in the district. The early sulfide veinlet-disseminated ores formed in the Silurian (450–430 Ma) and postdate the peak of the regional metamorphism in the region. During the middle Carboniferous (ca. 330 Ma), the rejuvenation of ore-forming processes resulted in the formation of native gold-bearing quartz veins. The constraints on the ages of gold mineralization of the Sukhoi Log-style deposits are of key importance for understanding their genesis and the features of evolution of the Bodaibo District as a gold-mining subprovince.
Keywords: BODAIBO DISTRICT; NORTHERN TRANSBAIKALIA; OROGENIC GOLD DEPOSIT; RB-SR AND40AR-39AR DATING; SUKHOI LOG; Палеозой::Силурийская; Палеозой::Каменноугольная; Paleozoic::Silurian; Paleozoic::Carboniferous